Low pressure microenvironments: Methane production at 50 mbar and 100 mbar by methanogens. (April 2018) - Mickol, Rebecca L.; Kral, Timothy A.
Abstract: Low pressure is often overlooked in terms of possible biocidal effects when considering a habitable environment on Mars. Few experiments have investigated the ability for microorganisms to actively grow under low pressure conditions, despite the atmosphere being a location on Earth where organisms could be exposed to these pressures. Three species of methanogens ( Methanobacterium formicicum, Methanosarcina barkeri, Methanococcus maripaludis ) were tested for their ability to actively grow (demonstrate an increase in methane production and optical density) within low-pressure microenvironments at 50 mbar or 100 mbar. M. formicicum was the only species to demonstrate both an increase in methane and an increase in optical density during the low-pressure exposure period for experiments conducted at 50 mbar and 100 mbar. In certain experiments, M. barkeri showed an increase in optical density during the low-pressure exposure period, likely due to the formation of multicellular aggregates, but minimal methane production (<1%). During incubation following exposure to low pressure, cultures of all species resumed methane production and increased in optical density. Thus, low pressure may not be a biocidal factor for certain methanogen species, with growth possible under low-pressure conditions. Results indicate that low pressure exposure may just be inhibitory during the exposure itself, and metabolism may resume following incubation under more ideal conditions. Further work is needed to address growth/survival under Mars surface pressures. Highlights: Methanobacterium formicicum is capable of active growth at 50 mbar and 100 mbar. Methanosarcina barkeri produces <1% methane at 100 mbar after 28 days. Methanosarcina barkeri increased in optical density at both 50 mbar and 100 mbar. Methanococcus maripaludis produces <1% at both 50 mbar and 100 mbar.